The role of stathmin expression in the differential diagnosis, prognosis, and potential treatment of ovarian sex cord-stromal tumors - Šafanda, Adam; Kendall Bártů, Michaela; Michálková, Romana; Švajdler, Marián; Shatokhina, Tetiana; Laco, Jan; Matěj, Radoslav; Méhes, Gábor; Drozenová, Jana; Hausnerová, Jitka; Špůrková, Zuzana; Škarda, Jozef; et al. (Diagnostic pathology, 2024)
BACKGROUND: Stathmin, a cytosolic microtubule-destabilizing phosphoprotein involved in the regulation of mitosis, is widely expressed in various malignancies and acts as an adverse prognostic factor. Our research analyzed its immunohistochemical expression on a large cohort of ovarian sex cord-stromal tumors, evaluating its potential utility in differential diagnosis, prognosis, and therapeutic application. METHODS: We examined 390 cases of ovarian sex cord-stromal tumors including 281 adult granulosa cell tumors (AGCT), 5 juvenile granulosa cell tumors (JGCT), 33 Sertoli-Leydig cell tumors (SLCT), 50 fibromas/thecomas (F/T), 11 Leydig cell tumors/steroid cell tumors (LCT/SterCT), 5 sex-cord stromal tumors NOS (SCST-NOS), 3 Sertoli cell tumors (SCT), and 2 sclerosing stromal tumors (ScST). Immunohistochemical analysis was performed using TMAs. RESULTS: Strong expression (> 50%) was observed in all cases of AGCT, JGCT, SLCT, SCST-NOS, SCT and 1 ScST. The other case of ScST exhibited mild expression (5-10%). The negative cases included exclusively F/T and LCT/SterCT, with F/T showing 24% of negative cases and LCT/SterCT comprising 64% of negative cases. CONCLUSION: The results of our study indicate that stathmin is neither a prognostic marker nor suitable for the differential diagnosis of challenging cases of ovarian sex cord-stromal tumors. However, its predictive value may be theoretically significant, as a decrease in stathmin expression potentialy influences response to chemotherapy treatment.
Keywords: gonadální stromální nádory; Sex Cord-Gonadal Stromal Tumors; Humans; diferenciální diagnóza; lidé středního věku; Biomarkers, Tumor; Female; nádory vaječníků; dospělí; Ovarian tumors; Ovarian Neoplasms; Stathmin; Diagnosis, Differential; lidé; Immunohistochemistry; imunohistochemie; Sex cord-stromal tumors; nádorové biomarkery; Adult; ženské pohlaví; Middle Aged; prognóza; Ovary; Prognosis; stathmin